Stereo Vision For Automated Image-Based Rendering - Chan, Sylvia Oi Yee (2004)
This research examines the techniques and methodology to automate Image-Based Rendering especially for the selection of significant features and solving the correspondence problem. We have shown that a strategy utilizing a range of image processing techniques is suitable for obtaining a good set of features. Results acquired are also consistent with previous research showing that discriminatory technique is required to obtain better coreespondence matches. The proposed algorithm demonstrated that it can be used to relieve users from stressful trials and errors. View synthesis has been demonstrated as a complement to streo vision as a step towards automated IBR.